Reengineering as an Innovative Basis to Reconstruct the Enterprise Management System - Prokhorova Viktoria V.; Bozhanova Olena V.; Yukhman Yaryna V. (Problemi Ekonomiki, 2020)
The actual value of the topic lies in the fact that nowadays the development of the world economic system is accompanied by innovative processes. Innovative development of enterprises is the only possible way to steer a country’s economy out of crisis. For most domestic industrial enterprises it is necessary to completely abandon the traditional enterprise management system or, at least, to transform it. Thus, it is becoming more and more actual to use methods and tools, which can foster innovative development in various activity areas at an enterprise, and the importance of reengineering as an innovative basis for the reconstruction of the enterprise management system is growing. The article aims at designing a conceptual foundation for reengineering as an innovative basis for the reconstruction of the enterprise management system. The authors reveal the content of reengineering and demonstrate its importance as the innovative basis for reconstructing the enterprise management system. The advantages of using reengineering are highlighted, the essence of reengineering as an economic process is identified. It is stated that reengineering allows providing a systematic and comprehensive approach to the innovative refocusing and restructuring of the enterprise management system as a whole, or of its individual functional components. The authors’ own definition of "reengineering" is offered. It is substantiated that reengineering allows reconstructing the enterprise management system in an innovative way. The need for the reengineering of the enterprise management system is shown. The conceptual basis of reengineering as an innovative basis for reconstructing the enterprise management system is proposed. The basis contains the principles, on which reengineering is grounded as an innovative basis for reconstructing the enterprise management system; and the main stages of reengineering. Reengineering as an innovative basis for reconstructing the enterprise management system involves holistic and systematic modeling and fundamentally changes the enterprise information flow; as a result, the organization structure is simplified, resources are redistributed, individual resources consumption is minimized, product life is reduced, the service quality and image are improved.